The Implementation of Storybird In Writing A Recount Text For Tenth Grade Students - Adini Amalia; Zainul Aminin (English Education Study Program Faculty of Teacher Training and Education, 2022)
The objective of this research is to investigate the effect of the implementation of Storybird in writing a recount text for tenth-grade students in Surabaya Senior High School. Storybird is a web application that supports the educational process. Storybird is a creative digital storytelling website that allows students to write their own stories using its writing feature. Therefore, this study aimed to determine if there was a significant difference in the post-test score for producing a recount text between the experimental and control groups after Storybird was implemented. A quantitative method was used in this study, and a true experimental randomized subject posttest-only control group was the design. The samples of this study were 61 tenth-grade students of Senior High School in Surabaya from the experimental class and control class. The data were gathered through post-test and analyzed by the t-test formula using SPSS computation. The findings of this study revealed that there was a significant difference in post-test scores between the experimental and control groups. The independent sample t-test results were significant at .012 < .05, showing a significant difference in the post-test results. In conclusion, it suggested that students can implement Storybird in writing a recount text.